Misconceptions of Physics Students on the Concept of Equilibrium of Rigid Bodies: A Case Study of Keku Culture - Batlolona, John Rafafy; Jamaludin, Jamaludin; Dulhasyim, Ashari Bayu P.; Silahooy, Stevi (FKIP Universitas Lampung, 2024)
Abstract: Physics scientists have paid serious attention to student misconceptions at various levels of education. The results show that learners have different ideas, which need to be more accurate about what is accepted in a scientific context. Student misconceptions in physics education have been assessed to date through various tests and found to be high. One less explored topic in physics teaching is the equilibrium of rigid bodies. Students consider this to be one of the most complicated topics. Therefore, this research used a test to measure students' misconceptions. This study aimed to determine the extent of student's misconceptions about the concept of equilibrium of rigid bodies in the case of Keku culture. This research is ethnographic research using a survey technique. One hundred prospective physics teachers participated in this study. Findings in the field showed that students experienced high misconceptions. It is because teachers at the lower level do not accustom students to learn from natural phenomena around them related to cultural concepts, and they are given scientific questions to search for and provide answers and solutions related to these natural phenomena. Teachers explore more conditions and physics problems in textbooks and less explore contextual things. Future researchers are advised that teacher teaching must be improved by developing physics teaching using appropriate strategies that can encourage students' understanding of concepts to reduce student misconceptions so that they impact students' academic performance. Keywords: concept understanding, misconceptions, ethnophysics, object equilibrium, keku.DOI: https://dx.doi.org/10.23960/jpmipa/v25i1.pp87-102